Por entre tramas e fios : o estresse e o bem-estar de professoras em uma escola pública de Uberlândia-MG - Paula, Andréia Cristina Rezende Rodrigues de (2009)
This research aims to analyze the stress and the welfare among teachers in a municipal public school of the city of Uberlândia-MG. Considering that the current moment is marked by social, political and cultural paradoxical changes, and also taking into account that many teachers live in the midst of situations of unease, of provocative cumulative stress, this study seeks to understand the welfare of teachers. It is intended to highlight the fact that despite the discomfort of the teachers and of the adversity falling on education and teaching, teachers resist, persisting in their profession and finding satisfaction, enjoyment and pleasure in the realization of a work. To uncover a "plot woven of many threads" the subjects and scenarios of the investigation were regarded as living systems, complex and unfinished, justifying the development of a qualitative research in everyday school life. The access to events and practices that highlight the experiences of welfare, conditions of stress and teacher discomfort, became possible, by means of systematic observations, descriptions and notes of field performed in the year 2008, and through reflexive interviews conducted with five female teachers who, despite the malaise, did not succumb to disappointment. The analysis of data collected in coexistence in space-time routine of school, with the teachers and their practices allowed the understanding that the problems that they face and the opportunities that are to face these are not just individuals. Moreover, many teachers cannot manage to reflect and realize that their experiences do not finish within the school or the classroom. Teachers` stress and welfare have also social, ethical and political components, and its corrosion effects are minimized or surpassed by means of very peculiar resistance (resilient ways to be and live). Therefore, they highlight the people subject of this research as builders of a story, at one time, collective and individual, able to make choices, create senses, transform and let them be transformed back, in the flow of each one`s own tension of everyday life, they are able to comply or resist, constituting themselves as teachers.